Anorexia Nervosa - Zipfel, Stephan; Stengel, Andreas; Giel, Katrin; Zipfel, Stephan; Stengel, Andreas; Giel, Katrin (Basel, Switzerland MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Anorexia nervosa is a common eating disorder affecting several functions of the body. Although our knowledge of the underlying mechanism has increased, therapeutic options are still limited. This Special Issue discusses several aspects of anorexia nervosa and covers a broad range of topics from the bench to the bedside.
English
Keywords: Medicine; Anorexia nervosa; treatment contracts; weight gain; inpatient treatment; survey; accelerometry; eating disorders; motor restlessness; physical inactivity; anorexia nervosa; cognitive behaviour therapy; manualised treatment; modules; worksheets; guidelines; evidenced-based; treatment; emotion regulation; males; drug-treatment; pharmacotherapy; medication; nutrition; comorbidity; complication; functional magnetic resonance imaging; disorder-specific stimuli; narrative review; immune system; inflammation; cytokines